Acute Toxicity of Cypermethrin and its Impact on Biochemical Alteration in the Fresh Water Fish Cirrhinus mrigala (Hamilton) and Protective Effect of Cardiospermum helicacabum (Linn) - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The cypermethrin (synthetic pyrethroids) has shown strong piscicidal activity in fresh water fish Cirrhinus mrigala for all exposure periods of 24, 48, 72, 96 and 120 hours. The acute toxicity value was found to be 150Âµg/l and 1/5 as used for of LC0 (30Âµg/l) was selected for sub lethal concentration. The biochemical parameters of Gill, Liver and Kidney tissue of Cirrhinus mrigala was studied, after 120 hrs, the dose depend alteration in the level of total protein, free amino acid and glucose. During recovery period, the level of biochemical components progressively increased indicating a problem recovered by Cardiospermum helicacabum. Hence, the pesticide intoxication has made a disturbance in normal functioning of cells with significant alteration in the fundamental biochemical mechanisms of fish.